2018
DOI: 10.1002/lio2.146
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach to the intrathoracic goiter

Abstract: ObjectiveIn a retrospective study, the authors analyzed the surgical approach to the intrathoracic goiter to avoid sternotomy or thoracotomy.MethodsWe selected 70 intrathoracic cases of multinodular goiter out of 988 cases of thyroidectomy and compared them with cervical goiter cases. Surgical technique, results, and postsurgical complications were assessed.ResultsThe analyzed cases presented the retrosternal goiter (n = 53; 75.7%), the retrotracheal goiter (n = 9; 12.8%), and the retroesophageal goiter (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
6
0
8
Order By: Relevance
“…Studies have reported mean weights of MNG to be 100-120 g and up to 180 g for cases of retrosternal extension. [10][11][12] Retrosternal extension rates vary depending on definition and classification. Recently, literature involving large case series place the true rate to be between 4.9% and 12.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported mean weights of MNG to be 100-120 g and up to 180 g for cases of retrosternal extension. [10][11][12] Retrosternal extension rates vary depending on definition and classification. Recently, literature involving large case series place the true rate to be between 4.9% and 12.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The size and weight of a MNG vary significantly globally due to difference in practice, regional and demographic variations. Studies have reported mean weights of MNG to be 100–120 g and up to 180 g for cases of retrosternal extension 10–12 . Retrosternal extension rates vary depending on definition and classification.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions are much vascularized and are adjacent to large vascular structures; for it is necessary to anticipate bleeding taking into account the possible difficulties in intubation and ventilation secondary to the distortion of the upper airway, in the pre-anesthetic assessment. 11 Most cases are euthyroid. In the presence of a toxic goiter, radioactive iodine treatment can be performed in patients with high surgical risk who are not candidates for the interventions described.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ITG is differently appreciated because their definition is not univocal. 1 The incidence appears to be declining, particularly in developed countries, due to iodized salt consumption; early diagnosis and treatment of cervical goiters. 2,3 Two types of ITG can be distinguished: secondary goiter (95-99% of the ITG) and primary or ectopic or autonomous goiter.…”
Section: Introductionmentioning
confidence: 99%